Expert system: Mushroom species / Nur Fuhaizah Mohammad Fawzi - Nur Fuhaizah, Mohammad Fawzi (2004)
Expert Systems are computer programs that use artificial intelligence to solve problems within a specialized domain that ordinarily requires human expertise. A very important aspect of helping mycologist with diagnosis of the mushroom health effects is the identification itself by using only the visible feature of the mushroom. Their identification, although very important, is often difficult. This thesis addresses this problem by providing an expert system that takes into consideration various factors about the mushroom, and presents identification as a possible solution. In order to achieve the purpose, the system uses Prolog, a logic programming. In this paper, chapter one outlines the introduction of the system. Chapter two describes the literature review. Chapter three discusses more details methodology. System analysis is described in chapter four. Chapter five describes the system design. Implementations are shown in chapter six and testing in chapter seven. Finally, chapter eight gives the conclusion.